2012
DOI: 10.1097/eja.0b013e32835422db
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, randomised, open-label, controlled trial evaluating equivalence of inhalational and intravenous anaesthesia during elective craniotomy

Abstract: Eudract 2007-005279-32.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 28 publications
1
69
2
5
Order By: Relevance
“…Recently, however, Citerio et al conducted a multicentre randomized equivalence trial comparing three different anesthetic regimens, including both volatile and propofolbased anesthesia, and found equivalent outcomes in intraoperative hemodynamics, quality of surgical field, and time to meet discharge criteria from the recovery room (i.e., Aldrete score 16 of 9). 17 Their results are supported by other similar randomized clinical trials. [18][19][20] Although not all aspects of these randomized trials may be generalizable to all centres, the balance of evidence does not support one technique over another in terms of more meaningful clinical outcomes such as time to awakening, early cognitive performance, and readiness for discharge from the recovery room.…”
Section: Short-term Outcomes: Perioperative Effects Of Anestheticssupporting
confidence: 81%
“…Recently, however, Citerio et al conducted a multicentre randomized equivalence trial comparing three different anesthetic regimens, including both volatile and propofolbased anesthesia, and found equivalent outcomes in intraoperative hemodynamics, quality of surgical field, and time to meet discharge criteria from the recovery room (i.e., Aldrete score 16 of 9). 17 Their results are supported by other similar randomized clinical trials. [18][19][20] Although not all aspects of these randomized trials may be generalizable to all centres, the balance of evidence does not support one technique over another in terms of more meaningful clinical outcomes such as time to awakening, early cognitive performance, and readiness for discharge from the recovery room.…”
Section: Short-term Outcomes: Perioperative Effects Of Anestheticssupporting
confidence: 81%
“…19 Our results suggest that in such patients, the rise in blood pressure during emergence from anesthesia can be attenuated by inserting a LMA before emergence, as less antihypertensive medication was needed in this subgroup. 20 The difference may be explained by our recording of any occurrence of cough during the awakening process. Although our study was not designed to enroll enough patients to detect differences in the subgroup of patients with controlled chronic hypertension, we find that our results are consistent with those of previous studies of anesthesia induction.…”
Section: Discussionmentioning
confidence: 97%
“…Observational and controlled studies demonstrated that the incidence of emergence agitation in patients after craniotomy was higher than that after other types of operations, such as ear, nose, and throat surgeries or ophthalmologic, abdominal, urologic, or vascular surgeries 5,2527. In our pilot study,5 we observed that emergence agitation was common in patients after elective craniotomy for brain tumors performed under general anesthesia.…”
Section: Discussionmentioning
confidence: 55%